Parent Attitude towards Children Education in South Punjab: An Analytical study in the Light of Islamic Thought - Zahid Zulfiqar; Muhammad Shabbir Ch.; Kamran Ishfaq (Pakistan Journal of Islamic Research)
Education is a basic, Islamic and universal right. Education is a capability that leads the society towards progress and prosperity as a whole. There are different serious issues of developing countries among them the most important is the educational exclusion of primary school age children. It is evident that millions of primary school age children are excluded from the basic education in Pakistan. Pakistan has a dynamic geography in which some areas enjoys more civic facilities whereas other are excluded from the basic facilities of life. South Punjab is also included in those areas in which people are facing active and passive exclusion. Due to the hegemony of Patriarchal structure and lack of Islamic knowledge parents prefer to son over daughter throughout their life. The present study was conducted in the three districts of South Punjab (i) Multan, (ii) Bahawalpur and (iii) Dera Ghazi Khan to examine the household head attitude towards children education. A sample of 975 household heads was selected by using the multistage random sampling. The interview schedule was used for gathering the quantitative data. The results indicated biased, non-Islamic and gendered attitude of the parents in which they preferred the son over daughter; majority of the respondents had more educational expectations from the male children; moreover they considered that girls should have to stay at home to perform the domestic chores. It was also found that the tradition and cultural values were also playing a negative role in the inclusion of girls education is South Punjab.